Laboratory Evaluation of Interactions in the Degradation of a Polypropylene Geotextile in Marine Environments. (3rd May 2018) - Carneiro, José Ricardo; Almeida, Paulo Joaquim; Lopes, Maria de Lurdes
Abstract : The long-term behaviour of geosynthetics applied in coastal engineering structures can be adversely affected by many agents. This paper studies the resistance of a nonwoven polypropylene geotextile against some degradation agents present in marine environments and evaluates the existence of interactions between them. For that purpose, the geotextile was exposed to some laboratory degradation tests: immersion tests (in seawater, deionised water, and sodium chloride 35 g·L −1 ), thermooxidation, and artificial weathering. The geotextile was (1) exposed separately to each degradation test and (2) exposed successively to combinations of two or three degradation tests. The damage caused by the degradation tests was evaluated by monitoring the tensile properties of the geotextile. Based on the changes occurred in tensile strength, reduction factors were determined. The reduction factors obtained directly in the multiple exposures were compared with those obtained by the traditional methodology for the combined effect of the degradation agents. The results, among other findings, showed the existence of relevant interactions between the degradation agents and showed that the reduction factors obtained by the traditional methodology were unable to represent accurately (by underestimating) the degradation occurred in the geotextile.